Digitization of Turkey Manuscripts - Selenay Aytaç (Türk Kütüphaneciliği)
This study intends to introduce the concept of manuscripts digitization and provide information to Turkish librarians working with Turkish manuscripts. After an introduction on the conceptual framework for digitization of manuscripts, focus will be on the technical requirements of digitization. The paper also intends to shed light on some of the international digitization projects that may offer relevant insights for the Turkish case. Finally, the paper will propose some solutions to improve the existing conditions of manuscripts in Turkey by using digitization.